Urgensi Persistensi Laba - Ng Husin; Ai Hendrani; Dadan Ramdhani; Popong Suryani (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
This study aim to obtain empirical evidence about book tax difference is proxied by temporer difference and institutional ownership to earning persistence in manufacturing companies on the Indonesian Stock Exchange. The method used is multiple regression analysis with program SPSS 25. The population in this study is manufacturing companies on the Indonesian Stock Exchange in 2017 until 2019. The Sampel in this research was done by purposive sampling methode, obtained as many as 67 companies used as a sampel with a predetermined criteria. The result indicate that the variable book tax difference and institutional ownership has significantly affect to earning persistence.